Temperature-sensitive liposome-mediated delivery of thrombolytic agents. (February 2015) - Saxena, Vishal; Gacchina Johnson, Carmen; Negussie, Ayele H.; Sharma, Karun V.; Dreher, Matthew R.; Wood, Bradford J.
Abstract Background: Clinical efficacy of thrombolytic drugs is limited by lack of specific delivery and requires large therapeutic doses which increase toxicity. Encapsulating these drugs in temperature-sensitive liposomes and applying hyperthermia to deliver thrombolytic agents locally to thrombus might theoretically favourably alter the therapeutic window. The objectives of this study were to formulate liposomes encapsulating thrombolytics and assess thrombolytic activity following hyperthermia. Methods: Three liposome formulations were investigated: temperature-sensitive liposome (TSL, DPPC:DSPE-PEG2000 (mol% 95:5)), low temperature-sensitive liposome (LTSL, DPPC:MSPC:DSPE-PEG2000 (mol% 85.3:9.7:5)), and traditional temperature-sensitive liposome (TTSL, DPPC:HSPC:Chol:DSPE-PEG2000 (mol% 55:25:15:5)). To characterise temperature-dependent release of high molecular weight cargo from each formulation, fluorescein-conjugated dextrans (70 kDa) were loaded and release was quantified via spectrophotometry. Staphylokinase (SAK), urokinase, and tissue-type plasminogen activator were also loaded individually into each liposome formulation. Leakage at 37 °C and release at 38–44 °C were quantified via chromogenic enzymatic activity assay. Clot lysis was evaluated by measuring mass of blood clots before and after thrombolytic liposome treatment. Results: The LTSL formulation had optimal release characteristics with maximum release at 41.3 °C. Release of dextrans from LTSLs was observed to be 11.5 ± 1.5%, 79.7 ± 1.6%, and 93.6 ± 3.7% after 15 min in plasma at 37°, 39°, and 41.3 °C, respectively. The SAK LTSL had the highest release/leakage ratio and demonstrated greater clot lysis. Conclusions: The SAK LTSL achieves significant clot lysis in vitro. When combined with local hyperthermia, the SAK LTSL potentially produces sufficient thrombolysis while minimising systemic side effects.